The state of infrastructure of the territories affected by the Chernobyl accident (in review of population and experts) - Vishniakova, Marharyta V. (Journal of the Belarusian State University. Sociology, 2021)
The article presents the assesment of satisfaction by the infrastructure of settlements located on the polluted lands in the context of achievement SDG 11 «Steady cities and settlements». On the basis of empirical data obtained during the implementation of the joint study of the Institute of Sociology of the National Academy of Sciences of Belarus and the Belarus State Economic University, the level of provision of settlements of the transport, social and housing and utilities infrastructure was determined. The quality of their services is assessed by the population and experts living in the territory contaminated with radionuclides. Insufficient level of provision of rural settlements of household services, sports and recreational facilities and organisations of housing and communal services has been revealed. Vulnerable aspects of health facilities included the organisation of reception of patients, the possibility of examination and treatment by doctors of narrow specialisation, as well as diagnostic examinations. The population and experts negatively assess road-, roadside- and sidewalks-clearing work in winter. They are concerned about the construction of roads, bridges, and the state of road surfaces, pay attention to the insufficient number of playgrounds and sports fields. The key problem in the work of public transport is associated with inconvenient schedules (insufficient amount of transport on the route).
Keywords: infrastructure; assessment of the quality of services; territories affected by the Chernobyl accident; contaminated areas